Pembelajaran Terpadu Model Webbed Melalui Permainan Edukatif untuk Meningkatkan Pemahaman Bilangan dan Kosakata Siswa Sekolah Dasar - Marianah, Dina; Sumarmi; Rahayuningsih, Sri; Anggraini, Ade Eka; Faizah, Siti (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
Early abilities in recognizing numbers and understanding vocabulary serve as a fundamental foundation in developing literacy and numeracy skills among first-grade elementary students. Unfortunately, the conventional subject-separated approach to learning often leads to a lack of student interest and difficulty in grasping concepts holistically. This study aims to explore the use of the Webbed-type integrated learning model based on educational games as a fun and developmentally appropriate method to improve students' understanding of numbers 1–10 and vocabulary mastery. Learning activities were conducted using media such as number snakes and ladders, number hopping, and number cards, under the theme “Let’s Play While Learning Numbers.” The research employed a descriptive qualitative method with data collection techniques including observation, interviews, documentation, and learning outcome tests. The study involved 32 first-grade students of SDN Klampok II, Tongas District, Probolinggo Regency. The results showed an increase in learning interest, active participation, and comprehensive understanding of numbers and vocabulary. These findings support the application of the Webbed model based on educational games as an effective and enjoyable alternative approach for early-grade elementary education.